2000
DOI: 10.1155/2000/416705
|View full text |Cite
|
Sign up to set email alerts
|

TNF-alpha but not IL-1alpha are Correlated with PGE1-Dependent Protection Against Acute D-Galactosamine-Induced Liver Injury

Abstract: Acute liver injury induced by D-GalN is correlated with an increased TNF-alpha release. Preadministration of PGE1 to D-GalN-treated rats exerted a priming effect on inflammatory cells to release enhanced levels of TNF-alpha but not IL-1alpha. These findings indicate that stimulation of TNF-alpha release may be involved in the acute D-GalN-induced liver injury and also in PGE1 protection from hepatotoxicity in clinical and experimental studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0
1

Year Published

2002
2002
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 25 publications
1
16
0
1
Order By: Relevance
“…Moreover, activated T cells can secrete many cytokines that may induce inflammation that exacerbate liver injury [34,35]. We examined the activation state of the T cells using CD69 as an activation marker by flow cytometry ( Fig.…”
Section: Secreted Il-1α Promotes T-cell Activationmentioning
confidence: 99%
“…Moreover, activated T cells can secrete many cytokines that may induce inflammation that exacerbate liver injury [34,35]. We examined the activation state of the T cells using CD69 as an activation marker by flow cytometry ( Fig.…”
Section: Secreted Il-1α Promotes T-cell Activationmentioning
confidence: 99%
“…Because TNF-␣ was suggested to mediate the development of GalN-hepatitis (6, 7) and Wallach et al (27) reported that preceding administration of TNF-␣ caused desensitization of mice to a lethal amount of TNF-␣, it would be likely that CBH desensitized the rats against GalN in the present study. The concentration of UDP-galactosamine in the liver of the rats increased rapidly after the injection of GalN (7)(8)(9)(10), and since the increase was accompanied by a reduction in the concentration of UTP and UDP-glucose in the liver, it is likely that the hepatotoxic action of GalN is mediated by suppression of RNA or glycoprotein biosynthesis caused by the deficiency of UTP or related compounds. Bauer et al (28) have reported inhibition of overall protein and glycoprotein secretion by GalN, and that was partially explained by inhibition of de novo protein synthesis.…”
Section: Discussionmentioning
confidence: 99%
“…Some investigators have indicated that an increase in blood endotoxin concentration after injection of GalN causes hepatic injury associated with secretion of cytokines, such as TNF-␣ and IL-6 from Kupffer cells ( 6,7 ). Endotoxin is a constituent of the cell wall of gram-negative bacteria, and since it may be absorbed from the gastrointestinal tract into the portal venous circulation, the intestinal microflora have generally been considered to be important for the development of GalN-hepatitis.…”
mentioning
confidence: 99%
“…Los niveles séricos de óxido nítrico se determinaron indirectamente mediante la cuantificación de sus productos finales nitrito y nitrato (13). En el ensayo el nitrato se convirtió a nitrito mediante la nitrato reductasa y el nitrito total se determinó mediante la reacción de Griess.…”
Section: Determinación De Los Niveles De óXido Nítrico Glutatión Y Munclassified